Ethnobotanical Study of Traditional Food in Newar Community of Kathmandu Valley, Central Nepal - Joshi, Nirmala (Journal of Plant Resources, 2022)
Socio-culture plays a significant role in conservation of indigenous knowledge and ethnic food in Nepal. Ethnic food makes the basis of diversified food which contributes to improve the health, besides food and nutrition securities. Documentation of plant based traditional food is crucial to enhance intercultural and intergenerational relations. Most of the traditional foods are prepared to celebrate rituals and culture using plants and plant products. This study gives a general overview of plant based traditional foods and rituals of Newar ethnic group inhabiting in Kathmandu Valley, Central Nepal. Data were gathered through ethnobotanical inventory, through interviews, participatory observations at festivals and ceremonies to document plants type, types of traditional food, consumption of traditional food in rituals, in addition to the challenges involved for indigenous knowledge preservation. Altogether 54 plant species were used for preparation of 45 types of traditional food. These traditional foods are consumed during celebration of more than 25 rituals and cultures of Newar ethnic group. Wild plants such as Blumea lacera, Centella asiatica, Choerospondias axillaris, Urtica dioica, etc. in particular occurred close to the areas where Newar community live and are mostly used for traditional food preparation. Other important plants were supplied by cultivation (i.e., domesticated species) and through markets. The young generation showed little interest in the consumption of traditional food. There is a great challenge to conserve traditional food and the related culture. Documentation of traditional knowledge about ethnic foods and their consumption in rituals will contribute for sustainable conservation of traditional food and culture for future generations.